The Development Of A Simple Harmonics Module In The Video Based Laboratory (VBL) - Sholikhah, Mar'atus; Partono, Partono; Salim, M. Barkah (JURNAL FIRNAS, 2020)
ABSTRACKA simple harmonic motion practicum module in video based laboratory (VBL) spring helps teaching and learning process in the classroom. The work procedure in the practicum module uses technology video to help for observation and analyze the physics concepts of simple harmonic motion in spring. By using video analysis tracker software, it can help teaching and learning process in the classroom such as practical activities. The purpose of this research is to produce practicum module based on video based laboratory (VBL). This research uses research and development method (R&D) and research uses the ADDIE.The results of the assessment by experts, namely the media experts are97.58%, material experts 95.58%, and linguists 95.58%. Appraisal by experts earns a percentage of 96.19%. The result of the assessment by experts obtaineda percentage of 96.19% and the results of the questionnaire given to student inthe module trials gained a percentage of 81.07%. The results of this research can be concluded that the video based laboratory (VBL) is practicum module is declared worthy of use in the process of practicum activities, has an agreeable response and has a positive effect on student practicum activities.Based on some of the above, this practical module has suggestions for users, namely, every computer used has installed tracker, the software trackerworks well and prepares tools for calibration. Keywords: Video Based Laboratory (VBL, and simple harmonic motion in spring, ADDIE.